Gum luck - Montijo, Rhode; Reynolds, Luke, 1980- (Montijo, Rhode. Gumazing gum girl!, 2017)
Gabby Gomez keeps her Gum Girl heroics secret from her parents, but there is a new villain in town and the city needs her to help.